Factors Associated with Dental Pain in Mexican Schoolchildren Aged 6 to 12 Years. (8th June 2017) - Escoffié-Ramirez, Mauricio; Ávila-Burgos, Leticia; Baena-Santillan, Elena Saraí; Aguilar-Ayala, Fernando; Lara-Carrillo, Edith; Minaya-Sánchez, Mirna; Mendoza-Rodríguez, Martha; Márquez-Corona, María de Lourdes; Medina-Solís, Carlo Eduardo
Abstract : Objective. To identify dental pain prevalence and associated factors in Mexican schoolchildren. Methods. This cross-sectional study included 1, 404 schoolchildren aged 6 to 12 years from public schools in the city of Pachuca de Soto, Hidalgo, Mexico. Data were collected through a questionnaire that addressed sociodemographic and socioeconomic factors, eating and dental hygiene habits, and behavior variables. The dependent variable was self-reported dental pain in the 12 months prior to the survey. Data were analyzed using nonparametric statistics and a binary logistical regression model. Results. Dental pain prevalence among the studied children was 49.9%. The variables associated in the final model (p < 0.05 ) were younger mother's age, higher socioeconomic level, absence of an automobile in the home, fried food, fruit intake, lower tooth brushing frequency, never having used mouthwash or not knowing about it, and parents/guardians with regular to high levels of knowledge about oral health and a regular or good/very good perception of their child's oral health. Conclusions. One in two children in the study had experienced dental pain in the twelve months prior to the survey. The association of socioeconomic variables with dental pain suggested inequalities among the children in terms of oral health.